Interleukin-4, interleukin-5, and interleukin-13 gene expression in cultured mononuclear cells from porcine circovirus type 2–vaccinated pigs after cells were challenged with porcine circovirus type 2 open reading frame 2 antigen (2013)
RESUMEN: Objective—To characterize the kinetics of interleukin (IL)-4, IL-5, and IL-13 secretion in peripheral blood and lymph node mononuclear cells isolated from porcine circovirus type 2 (PCV2)–vaccinated pigs after cells were challenged with PCV2 open reading frame 2 antigen. Animals—10 pigs. Procedures—5 pigs were vaccinated with a PCV2 vaccine and received a booster dose 3 weeks later. They were kept together with a similar group of 5 nonvaccinated pigs that served as controls. One week after the second vaccination, peripheral blood mononuclear cells (PBMCs) and excised retropharyngeal lymph node mononuclear cells (LNMCs) were isolated and cultured. Cells were then challenged by exposure to PCV2 open reading frame 2 and evaluated at 2, 12, 24, and 48 hours to determine the expression of IL-4, IL-5, and IL-13 via quantitative PCR assay. Changes in gene expression were analyzed relative to the results from analysis of the sample at 0 hours (calibrator). Results—All ILs were upregulated differently in LNMCs and PBMCs from vaccinated pigs. Lymph node mononuclear cells from vaccinated animals produced significantly more IL-4 mRNA than did PBMCs at 2, 12, and 48 hours (relative change: 2.8 vs −3.6, 13.0 vs 3.6, and 9.8 vs 1.8, respectively) and more IL-5 mRNA at 2, 12, 24, and 48 hours (relative change: 1. 2 vs −4.8, 2.2 vs 0.2, 3.2 vs −1.9, and 4.0 vs −3.6, respectively). Interleukin-13 mRNA reached its highest concentration at 24 hours but was 11.9-fold higher in PBMCs than in LNMCs.